Technicity as a Quality Indicator of Excellence in Gynaecology - Maha Al-Khaduri; Yahya Al- Farsi (Sultan Qaboos University Medical Journal, 2012)
Objectives: The objective of this study was to calculate the technicity index (TI) for hysterectomies at a tertiary care university hospital in Oman. Methods: This is a retrospective chart review of patients who had hysterectomies at Sultan Qaboos University Hospital (SQUH), a tertiary care university hospital. Profiles were reviewed for all patients who had hysterectomies at SQUH in the period 2003–2009. The cumulative frequencies for all types of hysterectomies were tallied and the year-specific TI was calculated. Results: Overall, we enumerated a total of 258 hysterectomies, of which 6 (2.3%) were laparoscopic assisted hysterectomies, 42 (16.3%) vaginal hysterectomies, and 208 (80.6%) total abdominal hysterectomies. The average TI was 19% (48/258), and it ranged from 11% to 24%. The trend of change fluctuated over the years starting with 16% (2003) and increasing gradually during 2004–2006, but then declining again during 2007–2008 (trend P value 0.02). This low and fluctuating trend was mainly attributed to the inconsistency in the availability of trained surgeons and laparoscopic equipment. Conclusion: TI at our institution can be improved by increasing the number of minimally invasive hysterectomies through providing more trained surgeons and laparoscopic equipment.